CERTAIN PERSONALITY TRAITS OF THE STUDENTS FROM THE UNIVERSITY OF PRIŠTINA (Heritage, 2020)
Having in mind the complexity of the various personalities, different papers on personality traits published by numerous authors, personality traits or personality dimensions as well as different theory models, we have tried here in this paper was to point out certain personality traits of the students from The University of Priština. In order words, paper shows research results conducted on students from the University of Priština, temporarily settled in Kosovska Mitrovica, from the 2014th up to the 2019th. The research has been conducted on students from different departments of the University of Priština, of both genders and of age 18 to 24. Theoretical approach used was one of the personality models: model Big Five, six-factor or model Big Five plus two. These personality models are accepted and current in science discourses in our country and abroad. Research results provide us with better understanding of certain personality traits of students from The University of Priština which allow us to undertake certain interventions and preventive measures in order to improve mental health of the students, but also for the improvement of their functioning in different life situations. Having in mind that students belong to adolescent period (or, to be accurate, to subperiod of late adolescence), which is considered to be the most important crisis in students’ development, better understanding of the certain personality traits may prove to be significant in giving psychological support and helping them to adopt to numerous and complex challenges during their studies, but also with the process of maturing which comes with this period.
Keywords: personality, personality traits, personality models, students, mental health